Mixed‐Valence Ce/Zr Metal‐Organic Frameworks: Controlling the Oxidation State of Cerium in One‐Pot Synthesis Approach. (6th May 2021) - Ronda‐Lloret, Maria; Pellicer‐Carreño, Isaac; Grau‐Atienza, Aida; Boada, Roberto; Diaz‐Moreno, Sofia; Narciso‐Romero, Javier; Serrano‐Ruiz, Juan Carlos; Sepúlveda‐Escribano, Antonio; Ramos‐Fernandez, Enrique V.
Abstract: The preparation of MOFs including a metal with an easily exchangeable oxidation state, while maintaining the same crystal structure and stability, is of paramount importance for myriad applications. In this work, a new synthesis method is reported that can be used to prepare Ce/Zr‐MOFs (UiO‐66 structure) having only Ce(III), a mixed‐valence Ce(IV)/Ce(III), or only Ce(IV) cations, as desired. The materials are characterized using a large number of techniques, including X‐ray absorption and X‐ray photoelectron spectroscopies. Abstract : In this contribution, a synthetic method has been developed to introduce Ce cations with the desired oxidation state (Ce3 + or Ce4 +) in the structure of UiO‐66(Zr). This has only been possible with the help of powerful characterization techniques such as X‐ray absorption, which confirm the success of the synthetic method.